Broadening the paradigm of laminin α2-related muscular dystrophy: A case of partial merosin deficiency with compound heterozygous variants - Azita Tavasoli; Shayan Eghdami; Maryam Kachuei; Saman Rouzbeh (SAGE Open Medical Case Reports)
Laminin α2-related muscular dystrophy is a rare autosomal recessive condition caused by mutations in the LAMA2 gene, with clinical presentations ranging from severe congenital forms to milder phenotypes resembling limb-girdle muscular dystrophy. We report a case of a 4-month-old girl presenting with delayed head control, axial hypotonia, and proximal muscle weakness, while cognitive and cardiac functions remained preserved. Laboratory evaluations revealed elevated serum creatine phosphokinase and lactate dehydrogenase levels. Muscle biopsy demonstrated dystrophic changes and partial merosin deficiency. Whole-exome sequencing identified two heterozygous variants in LAMA2: a known missense variant ( c.6548T>G; p.L2183R ) and another likely pathogenic missense variant ( c.6979G>T; p.G2327 ). However, targeted parental testing and quantitative PCR confirmed c.6548T>G as paternally inherited and revealed a novel heterozygous frameshift deletion ( c.291delC ) maternally inherited, consistent with compound heterozygosity in trans. The c.6979G>T variant was not confirmed as part of the disease-causing allele combination. In silico analyses supported the pathogenicity of the novel deletion. The patient received multidisciplinary care, including individualized physical and occupational therapy, and her family received genetic counseling. This case highlights the diagnostic value of early genetic testing, the importance of confirming inheritance patterns, and the contribution of novel LAMA2 mutations to the understanding of genotype–phenotype correlations in laminin α2-related muscular dystrophy.